Immunoscintigraphy with three step monoclonal pretargeting technique in diagnosis of uveal melanoma: preliminary results. Issue 1 (January 1994) - Modorati, G; Brancato, R; Paganelli, G; Magnani, P; Pavoni, R; Fazio, F
Abstract : Several problems still limit the full use of the diagnostic potential of immunoscintigraphy (IS) with technetium-99m labelled monoclonal antibodies (MoAbs) 225-28S directed to high molecular weight melanoma associated antigen (HMW-MAA). The principal problem is the unfavourable ratio of tumour to non-tumour activity (T/nT), due to the poor tumour uptake and the high aspecific uptake of the tissue surrounding the tumour. Recently, it was demonstrated that using the tumour pretargeting technique based on the injection of monoclonal antibody and the avidin/biotin system (three step immunoscintigraphy), an improvement in the T/nT ratio can be obtained in patients with carcinoembryonic antigen secreting tumours. The aim of this study was to compare the diagnostic sensitivity of traditional immunoscintigraphy with that of three step immunoscintigraphy in seven patients with uveal melanoma. All the patients underwent immunoscintigraphy with MoAb 225.28S radiolabelled with technetium-99m, and a three step immunoscintigraphy 1 week later. No patients demonstrated immediate toxic effects after receiving the reagents, no matter which of the two methods was used. The traditional immunoscintigraphy had a diagnostic sensitivity of 71.4%, diagnosing five out of seven melanomas tested. The three step study detected all the melanomas examined (7/7) with a diagnostic sensitivity of 100% and showed a drastic reduction in background. The preliminary results confirm the feasibility of visualising the uveal melanoma and show that the three step immunoscintigraphy is more diagnostically sensitive than traditional immunoscintigraphy, particularly in small lesions.